A scoping review of the relationship between students’ ICT and performance in mathematics and science in the PISA data - Odell, Bryce; Cutumisu, Maria; Gierl, Mark (Social psychology of education, 2020)
This scoping literature review examines the relationship between ICT and performance scores in mathematics and science for students around the world included in the PISA assessment. In this review we examined 25 publications and showed that the relationship between ICT and academic achievement is not consistent. The different types of ICT revealed different relationships with performance, depending on the subject and country of the students being examined. Although there is a lack of overall consensus, it seems that moderate use, rather than high or no use of ICT, can positively predict academic scores. Although autonomy, interest, and use of ICT as a topic in conversations have been less scrutinized by researchers, they seem to positively predict both mathematics and science scores in 15-year-old students. Implications, limitations, and recommendations are discussed.